Using 'may contain' labelling to inform food choice: a qualitative study of nut allergic consumers - Gowland M Hazel; Raats Monique M; Shepherd Richard; Leftwich Jo; Muncer Kate; Barnett Julie; Grimshaw Kate; Lucas Jane S (BMC, 2011)
Abstract Background Precautionary 'may contain' warnings are used to indicate possible allergen contamination. Neither food safety nor foods labelling legislation address this issue. The aim of this study is to understand how peanut and nut allergic adults interpret 'may contain' labelling and how they use this information when purchasing food. Methods Qualitative methods were used to explore both behaviour and attitudes. The behaviour and 'thinking aloud' of 32 participants were recorded during their normal food shop. A semi-structured interview also explored participants' views about 13 potentially problematic packaged foods. Transcribed data from these tasks were analysed to explore the interpretation of 'may contain' labelling and how this influenced food choice decisions. Results Peanut and nut allergic individuals adopt a complex range of responses and strategies to interpret 'may contain' labelling. Many claimed such labelling was not credible or desirable; many ignored it whilst some found it helpful and avoided products with all such labelling. Interpretation and consequent decisions were not only based on the detail of the labelling but also on external factors such as the nature of the product, the perceived trustworthiness of the producer and on the previous experience of the nut allergic individual. Conclusions 'May contain' labelling was interpreted in the light of judgements about the product, producer and previous personal experience. It is vital that these interpretation strategies are taken into account by those responsible for labelling itself and for the provision of advice to nut allergic individuals. Suggestions to improve labelling and advice to the allergic individual are considered.